The Relationship Between Length of Surgery and the Occurrence of Shivering in Sectio Cesarea Patients using Spinal Anaesthesia - Novitasari, Dwi; Angin, Sandri E Perangin; Burhan, Asmat (GLOBAL HEALTH SCIENCE GROUP, 2024)
Sectio cesarea is a surgical procedure to deliver a fetus with an incision on the abdominal wall and uterine wall of the mother. Spinal anesthesia in SC can cause shivering. The risk of shivering can occur due to the length of surgery. Objective: To determine the relationship between the length of surgery and the incidence of shivering in SC patients. Methods: This research design uses a correlation with a cross-sectional approach. Sampling technique with Purpose sampling of 115 patients who performed spinal anesthesia on SC patients. The research instrument contains patient data, which includes age, length of surgery, and incidence of shivering. This study used an observation sheet to measure the incidence of shivering in patients undergoing cesarean section, and the results of the data were analyzed using the chi-square test. Results: Most respondents were 21-35 years old (81.7%), the majority of the duration of surgery was less than 60 minutes with 67 patients (58.3%), and the incidence of shivering was 62 patients (53.9%). Conclusion: There is a relationship between the length of surgery and the occurrence of shivering in cesarean section patients who use spinal anesthesia at Efarina Etaham Berastagi Hospital with a p-value of 0.008 (<0.05).